"Holy Cow, My Irony Detector Just Exploded!" Calling Out Irony During The Coronavirus Pandemic. (2nd January 2021) - Gibbs, Raymond W.
ABSTRACT: One of the compelling events during the 2020 spring coronavirus pandemic is the extent to which people call-out "irony" in regard to the speech and actions of other individuals, as well as, in some cases, their own behaviors. These frequent call-outs are evidence of the cognitive realization of some discrepancy between prior expectations and unfolding reality, but also reveal people's communicative efforts to persuade others to adopt a negative view of those individuals who are responsible for the irony. This article explores several examples of irony call-outs in the context of both verbal irony and situational irony in the midst of the pandemic. My analysis suggests that what is considered to be "irony" always depends on the level of analysis from which such judgments are made. Irony may be salient from a personal point of view but non-ironic from a social/cultural perspective, and vice-versa. Our sense that an event is ironic may also change over time. Some call-outs of irony even focus on future "ironic opportunities" that would address different economic, environmental, and social justice challenges. These observations suggest several implications for theory and research on irony.